Effectiveness and Safety of Intravenous Sedation with Propofol in Non-Operating Room Anesthesia (NORA) for Dental Treatment in Uncooperative Paediatric Patients - Gianmaria Fabrizio Ferrazzano; Tiziana Cantile; Martina Quaraniello; Michele Iannuzzi; Daniela Palumbo; Giuseppe Servillo; Silvia Caruso; Fabiana Fiasca; Aniello Ingenito (MDPI AG, 2021)
Background: Uncooperative children require sedative approach for dental treatment. The aim was to assess the effectiveness of Propofol in "Non-Operating Room Anesthesia" (NORA) for paediatric dental treatment; intraoperative side effects; postoperative side effects; post-discharge effects. Methods: a prospective study, involving 109 uncooperative children undergoing sedation in NORA using Propofol for dental treatment, was performed. Working sessions, success/failure, intraoperative and postoperative side effects, number of treatment; type of procedure were assessed. Parents completed a post-discharge questionnaire on: pain; crying; fever; vomiting; headache; drowsiness; excitability; irritability; ability to eat; drugs and medical care needing. Results: Success: 96.7%. Intraoperative side effects: 33.3%. Postoperative side effects: 6.4%. Statistically significant association between: intraoperative side effects and age (p = 0.001), health status (p = 0.0007), weight (p = 0.038), respectively; intraoperative side effects and number/ type of dental treatment (p = 0.0055) and scaling (p = 0.0001), respectively. For post-discharge questionnaires, statistically significant association between: age and crying (p = 0.0001) and headache (p = 0.002), respectively; health status and crying (p = 0.015) and drugs needing (p = 0.04), respectively; weight and crying (p = 0.0004); extraction and pain (p = 0.0001) and crying (p= 0.0073), respectively; scaling and crying (p = 0.04), excitability and irritability (p = 0.03), respectively. Conclusion: Propofol in NORA was effective with minimal side effects.